A 20-year spatio-temporal analysis of 3D radar-based hail tracks in Germany: trends and regional differences - Mohr, Susanna; Tonn, Mathis; Augenstein, Markus; Sperka, Christian; Kavil Kambrath, Gokul; Kunz, Michael (Frontiers in Environmental Science, 2026)
For a long time, the lack of archived radar data in Germany prevented comprehensive, long-term studies of convective storms. However, the recent availability of a 20-year, homogeneous dataset based on 16, and in some years 17, single-polarization C-band radars now allows for consistent, national-scale analyses. This dataset provides a solid foundation for more precise hail statistical assessments and long-term hail frequency estimation, including potential trends. A tracking algorithm (TRACE3D), which was specifically modified to detect severe convective cells with the potential to produce hail, was used to identify 15,577 potential hail tracks (PHTs) during the summer half-year period from 2005 to 2024. Validation against building insurance data shows that the modified TRACE3D algorithm performs reasonably well and can adequately reproduce hail statistics in Germany. The spatial distribution of the PHTs reveals distinct regional patterns, including a north-to-south gradient influenced by the proximity to seas and orographic features. The highest hail frequency occurs south of Stuttgart and over the Bavarian Prealps. Most tracks are shorter than 40 km and last no more than 75 min (both at the 75th percentile). Nearly 60% of the tracks show a propagation direction from southwest to northeast, which aligns with typical mid-tropospheric conditions favoring convection. Furthermore, half of the days with PHTs are associated with atmospheric blocking regimes, such as Scandinavian, European, or Greenland blocking. Hail events in Germany are unevenly distributed in time. Sixty-three percent of days record no PHTs, and there are only occasional periods of intense hail activity with many tracks per day. While many hail days tend to be isolated (40%), under certain weather conditions, serial clustering of several hail days can form. However, such episodes rarely last more than 2 weeks and are often associated with prolonged blocking. Trend analyses show a high annual variability in PHTs with no clear trend for entire Germany. However, significant regional differences emerge: northern and central Germany show a decreasing tendency in PHT occurrence, whereas southern Germany exhibits a significant increase.